Inheriting Syria : Bashar's trial by fire - Leverett, Flynt Lawrence (Brookings Institution Press, 2005)
"A detailed analytic portrait of Syria under the Asad dynasty, offering a new strategy for achieving American foreign policy and security objectives in the Middle East, largely independent of the Arab-Israeli peace process"--Provided by publisher